2011
DOI: 10.1007/s11524-011-9571-8
|View full text |Cite
|
Sign up to set email alerts
|

Unsafe Injection and Sexual Risk Behavior among Injecting Drug Users in Georgia

Abstract: Injection drug users (IDUs) are at risk for acquiring human immunodeficiency virus (HIV) through parenteral and sexual transmission. In this paper, we describe the prevalence and correlates of unsafe drug injecting and sexual behaviors among IDUs recruited across five cities in Georgia in 2009. IDUs were administered a questionnaire collecting information on demographics, drug use, sexual behaviors, and HIV testing behaviors. Correlates of risky injecting and sexual behaviors were determined using logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
4
8
0
Order By: Relevance
“…Similar to other recent reports (Chikovani et al, 2011) direct needle sharing was not high among study participants (Table 3); the most common unsafe injection behavior at baseline was sharing a cooker and dividing the solution using one syringe. Buprenorphine injection in Georgia generally occurs in groups of 3–4 people who dissolve one 8 mg tablet in a water and then, using a large volume syringe, divide the solution by front- or back-loading into smaller individual syringes (Javakhishvili et al, 2011; Otiashvili et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Similar to other recent reports (Chikovani et al, 2011) direct needle sharing was not high among study participants (Table 3); the most common unsafe injection behavior at baseline was sharing a cooker and dividing the solution using one syringe. Buprenorphine injection in Georgia generally occurs in groups of 3–4 people who dissolve one 8 mg tablet in a water and then, using a large volume syringe, divide the solution by front- or back-loading into smaller individual syringes (Javakhishvili et al, 2011; Otiashvili et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…However, there is also a need to understand and address sexual transmission of HIV infection among IDUs and their sexual partners. While a few studies from Indonesia and United States of America (USA) have demonstrated no association between injecting and sexual risk behaviors [17,18], other international studies conducted in South Africa and USA have established this association [19-23]. Although some Indian studies have investigated the sexual risk behaviors of IDUs [2,4,6,24,25], none have attempted to analyze the associations between injecting and sexual risk behaviors of IDUs in Northeast India, where injecting drugs remains an important route of HIV transmission [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…This was related to either collection of money for expensive 8 mg buprenorphine tablet, to be later divided and injected by, usually, four individuals, or to predetermined division of functions/labor (money, procurement of precursors, cooking) among group members in case of preparation of home-made stimulants and opioids [11]. In all these instances injection happened within a group of 3–5 drug injectors with apparently little direct sharing, but frequent indirect sharing via common container, cotton filters, and large volume syringe for division (front or back loading) of the produced substance [9, 40]. …”
Section: Discussionmentioning
confidence: 99%